2008
DOI: 10.1681/asn.2008030315
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Extracellular Phosphoglycoprotein Inhibits Phosphate Transport

Abstract: The role of putative humoral factors, known as phosphatonins, in phosphate homeostasis and the relationship between phosphate handling by the kidney and gastrointestinal tract are incompletely understood. Matrix extracellular phosphoglycoprotein (MEPE), one of several candidate phosphatonins, promotes phosphaturia, but whether it also affects intestinal phosphate absorption is unknown. Here, using the in situ intestinal loop technique, we demonstrated that short-term infusion of MEPE inhibits phosphate absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 43 publications
3
41
0
1
Order By: Relevance
“…Indeed, several studies report FGF23 interacts with KLOTHO to directly suppress renal NPT2A expression in the brush border of renal proximal convoluted tubules (45). Likewise, ASARM peptides (in vitro) and MEPE (in vivo and in vitro) directly inhibit Na-dependent P i uptake in renal cells (14,36,49,51,52,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies report FGF23 interacts with KLOTHO to directly suppress renal NPT2A expression in the brush border of renal proximal convoluted tubules (45). Likewise, ASARM peptides (in vitro) and MEPE (in vivo and in vitro) directly inhibit Na-dependent P i uptake in renal cells (14,36,49,51,52,56).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies confirm fulllength MEPE inhibits intestinal/renal phosphate transport and mineralization in vivo and in vitro (14,36,49,52,56). These studies consist of bolus injections or direct perfusion in rats and mice using recombinant MEPE protein.…”
mentioning
confidence: 99%
“…Additionally, the accumulation of ASARM peptides can directly inhibit Na C -dependent P i uptake in the kidney, as has been shown both in vivo and in vitro, thus exacerbating the upregulation of FGF23 expression, the downregulation of 1,25(OH) 2 D 3 and the inhibition of hypophosphataemia observed in XLH, ARHR and ADHR , Dobbie et al 2008, Marks et al 2008, David et al 2010, Shirley et al 2010. The decrease in 1,25(OH) 2 D 3 provides a feedback loop for increased PHEX expression through the increased expression of a 100 kDa transcription factor, a requirement for this PHEX expression (Ecarot & Desbarats 1999).…”
Section: The Asarm Hypothesis and Bone Diseasesmentioning
confidence: 93%
“…The administration of the MEPE-ASARM peptide in vitro and in vivo can inhibit the uptake of P i . This is likely through a decreased expression of the type II sodium-dependent P i cotransporter NPT2a, or through the promotion of FGF23 expression, a potent inhibitor of P i (Liu et al 2007, Dobbie et al 2008, Marks et al 2008, Martin et al 2008, David et al 2010, Shirley et al 2010. It has, however, been suggested that MEPE may have a direct effect on matrix mineralisation outwith the supply and demand of P i .…”
Section: Matrix Extracellular Phosphoglycoproteinmentioning
confidence: 99%
“…sFRP4 acutely downregulates renal phosphate reabsorption and NaPi-IIa abundance in rat kidney [11], however, mice lacking sFRP4 adapt normally to changes in phosphate intake [18]. MEPE reduces renal phosphate reabsorption [21,31] and MEPE deficient mice display hyperphosphatemia with elevated expression of NaPi-IIa consistent with a phosphaturic role of MEPE [20]. However, the role of MEPE in the acute renal adaption to changes in dietary phosphate intake has not been determined.…”
Section: Regulatory Network In the Renal Adaption To Dietary Phosphatmentioning
confidence: 99%